Aspectos ecossilviculturais em plantios de Monteverdia ilicifolia (Mart. ex. Reissek) Biral e Bauhinia forficata Link. - Peccatti, Aline (2021)
Knowledge about ecological and silvicultural aspects of native tree species is essential to understand their behavior in the field in order to manage them properly, especially when the objective is to insert them in the context of agricultural production. Thus, this research aimed to evaluate ecological and silvicultural aspects of Monteverdia ilicifolia and Bauhinia forficata plants produced with Trichoderma and vermicompost and the possible residual effects of these biostimulants on the vegetative growth of plants in the field. The research was conducted at the Center for Research in Forests, Santa Maria, RS, and consisted of four trials, arranged according to the species (M. ilicifolia and B. forficata) and the biostimulants (vermicompost and Trichoderma) used in the production phase of the seedlings. The treatments tested comprised seedlings of both species, produced in a greenhouse, in a substrate composed of different proportions of vermicompost (T20: 20%; T40: 40%; T50: 50%; T60: 60% and T80: 80%) and soil, and in commercial substrate inoculated with Trichoderma strains (strains T1 and T2: T. asperelloides; strains T13 and T33: T. harzianum and strain T10: T. viride) and control treatments (without vermicompost (T0) and without Trichoderma). At 330 days after seeding, the seedlings were transplanted to the field, with a spacing of 4 m x 3.5 m. The essay was installed following a randomized block design. Statistical analyzes were performed separately for each essay, in factorial scheme (biostimulant x time) with split plots over time. Initial surviral (one month after planting – m.a.p) and final surviral (43 months after planting), height, stem diameter and stem height/diameter ratio at the time of planting, one month after planting and half-year up to 43 months after planting as well as the periodic annual increment in height and diameter stem at the end of the evaluations (43 m.a.p) were evaluated. For M. ilicifolia, the number of leaves were also evaluated half-year up to 25 m.a.p. and the number of branches from the base to 43 m.a.p. Survival rates in the field were high for both species. For M. ilicifolia, T1, T2 (T. asperelloides) strains and T10 (T. virens) strain do not show residual effect of the application on the growth of M. ilicifolia under field conditions; The vermicompost has a residual effect on the height variable of M. ilicifolia at 43 months after planting; Substrates composed of T40, T50 and T60 proportions are suitable to stimulate the initial growth of seedlings; The reproductive phenology decreases increment in the plant height and stem diameter of the M. ilicifolia; The flowering activity index has increased more significantly than the fruiting activity index over the years, but still insufficient to infer on the action of biostimulants. Studies that assess the floral typology of each individual can be useful for a better understanding of reproductive dynamics. For B. forficata, T1 and T2 (T. asperelloides) strains, T13 and T133 (T. harzianum) strains and the use of vermicompost in the composition of substrates promote the initial growth in height and stem diameter of B. forficata seedlings; residual effects of the application of Trichoderma spp. and vermicompost in the production of seedlings are effective in a period corresponding to the transposition to field planting (330 days after sowing); The ecological characteristics of the species influence the vegetative growth.